CLINICAL CORRELATIONS BETWEEN THE CLASS V RESTORATIONS AND PROXIMAL PERIODONTAL ILLNESS- REVIEW - Iren Moraru; Ana Maria Râcă; Dora Popescu; Sorina Solomon; Lucian Dragomir (Romanian Dental Association for Education, 2019)
There is a strong correlation between the presence of class V defects restored or not and the inflammatory gingival reaction nearby. It has been studies extensively, considering that it may occur a vicious circle where the presence of a faulty obturation, a cavity, a recession, a certain material in obturation may irritate the gingiva and this inflammation may concur to cavity occurrence, certain plaque retention, low pH levels.